Clinical Outcomes Associated with Medication Regimen Complexity in Older People: A Systematic Review. Issue 4 (19th December 2016) - Wimmer, Barbara C; Cross, Amanda J; Jokanovic, Natali; Wiese, Michael D; George, Johnson; Johnell, Kristina; Diug, Basia; Bell, J. Simon
Abstract : Objectives: To systematically review clinical outcomes associated with medication regimen complexity in older people. Design: Systematic review of EMBASE, MEDLINE, International Pharmaceutical Abstracts, Cumulative Index to Nursing and Allied Health Literature, and the Cochrane library. Setting: Hospitals, home, and long‐term care. Participants: English‐language peer‐reviewed original research published before June 2016 was eligible if regimen complexity was quantified using a metric that considered number of medications and at least one other parameter, regimen complexity was calculated for participants' overall regimen, at least 80% of participants were aged 60 and older, and the study investigated a clinical outcome associated with regimen complexity. Measurements: Quality assessment was conducted using an adapted version of the Joanna Briggs Institute critical appraisal tool. Results: Sixteen observational studies met the inclusion criteria. Regimen complexity was associated with medication nonadherence (2/6 studies) and higher rates of hospitalization (2/4 studies). One study found that participants with less‐complex medication administration were more likely to stop medications when feeling worse. One study each identified an association between regimen complexity and higher ability to administer medications as directed, medication self‐administration errors, caregiver medication administration hassles, hospital discharge to non‐home settings, postdischarge potential adverse drug events, all‐cause mortality, and lower patient knowledge of their medication. Regimen complexity had no association with postdischarge medication modification, change in medication‐ and health‐related problems, emergency department visits, or quality of life as rated by nursing staff. Conclusion: Research into whether medication regimen complexity is associated with nonadherence and hospitalization has produced inconsistent results. Moderate‐quality evidence from four studies (two each for nonadherence and hospitalization) suggests that medication regimen complexity is associated with nonadherence and higher rates of hospitalization.